2020
DOI: 10.1504/ijebr.2020.109152
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial inclusion on consumers saving and borrowing behaviours: a retrospective cross-sectional evidence from the UAE and the USA

Abstract: This paper highlights the impact of financial inclusion on individuals' borrowing and saving decisions in the United States and the United Arab Emirates. It does so, using data from the 2014 Global Financial Inclusion database, and an empirical strategy consisting of first testing the significance of the joint bivariate model over its binary conterparts using the Lagrange multiplier test, followed by a contrast between the fully-parametric and semi-parametric specifications of the saving and borrowing equation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
5
3
4
Order By: Relevance
“…Furthermore, Arslanian and Fischer ( 2019 ) suggested that financial innovation, particularly technological advancement in providing financial services, results in easy access to the unbanked population in the formal financial system. Similar findings are available in the literature (Agoba et al, 2017 ; Amoah et al, 2020 ; see, for instance, Niankara and Muqattash, 2020 ). So it is possible to believe that financial innovation broke the chain of demographic and social attribute issues that are dragging people to avail financial benefits.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Furthermore, Arslanian and Fischer ( 2019 ) suggested that financial innovation, particularly technological advancement in providing financial services, results in easy access to the unbanked population in the formal financial system. Similar findings are available in the literature (Agoba et al, 2017 ; Amoah et al, 2020 ; see, for instance, Niankara and Muqattash, 2020 ). So it is possible to believe that financial innovation broke the chain of demographic and social attribute issues that are dragging people to avail financial benefits.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Indeed, unlike the case of high‐income countries such as USA and UAE, where Niankara and Muqattash (2020) found government transfer deposits to not significantly influence saving behaviour, here we found that government transfer receipts increase individual' MPS by 11.6% within ECOWAS. This finding further corroborates with Keho (2019), which reports domestic savings to significantly influence economic growth in both, short and long run in Ivory Coast.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, within ECOWAS country members, accounting for individual income level, education does not appear to influence savings behaviour significantly. This finding contrasts with the 20.9% education‐based gradient reported by Niankara and Muqattash (2020) in the context of the US and UAE. This observation might however be explained by the fact that typically, in high‐income countries, individuals with the most education are the main drivers of economic activities, through active participation in the formal sector, whereas in low‐income countries, much of economic activities are concentrated in the informal sector, where little education is needed.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations